Peran Media Sosial dalam Sektor Penjualan Langsung untuk Meningkatkan Kepuasan Pelanggan: Studi Kasus pada Butik Ghaisan (Ghaisan Fashion Gallery) - Pratiwi, Fitriyanti; Agus, Mas; Gushevinalti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Social media has changed the way we interact with information and with the people around us. Platforms such as Facebook, Tiktok, Instagram, Twitter and YouTube have become popular means for individuals and companies to share, communicate and promote an organization's products and services. Within the direct selling sector, social media has opened up endless new opportunities for businesses to market and sell their products to potential customers. The purpose of this study is to analyze the role of social media in the direct selling sector and evaluate the impact of using social media on customer satisfaction at Ghaisani Boutique. This research method takes a qualitative approach, which aims to understand and describe phenomena in depth through data collection and analysis that focuses on the context and meaning of the subject under study. The results of the study show that social media provides significant benefits for Ghaisani Boutique (Ghaisani Fashion Gallery) in increasing the intensity of their promotion through online media, which has a positive impact on increasing their turnover. By leveraging creative and diverse social media features, Ghaisani Boutique can reach potential customers from various segments and expand their market coverage. In this case, social media is an effective means of building brand awareness, increasing customer engagement, and obtaining valuable feedback for better business development in the future. And what is no less important, Ghaisani Boutique has managed to build a sizable customer list through list building that continues to grow over time. By providing maximum service and responding quickly to feedback from the audience, Ghaisani Boutique can create high customer satisfaction. As a result, company promotions can run organically, driven by customers who voluntarily provide support through likes and shares of any content shared by the marketing team.